(untitled) (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
A “Boxer” fracture is the fracture of the neck of the fifth metacarpal due to direct trauma to the fist. One of the most common causes is punching an object with a closed fist during a fight or punching a hard object. As many as 33% of patients with hand fractures are metacarpal fractures, the majority involving the fifth metacarpal. Men dominate the incidence of "boxer fracture". The peak incidence is at the ages of 10-29 years. Conservative management of "boxer fracture" tends to dislocate easily, causing flexion contractures in the finger joints and skin necrosis in the hands. Some researchers suggest surgical treatment because functionally and aesthetically the results look better. In addition, factors such as longitudinal shortening, angulation, malrotation, bone loss and soft tissue injury are indications for internal fixation. The population of boxer fracture patients mostly occurs in males of young age or productive age working with a high economic burden, so that faster recovery of hand activity is ensured. Internal fixation is an option so that the hands immediately function to work. The choice of internal fixation depends on the type and location of the fracture, soft tissue damage, age and occupation. Several internal fixation modalities for boxer’s fractures such as percutaneous fixation with Krischner wire, cerclage with suture wire, intermedullary nail, plate screw to arthroplasty. By knowing the implant choice strategy according to the type and location of the fracture, soft tissue damage, age, and occupation, it is hoped that it will provide the best functional and aesthetic results in the treatment of boxer fractures.